2005
DOI: 10.1016/j.ymthe.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Adeno-associated Virus 8-Pseudotyped Vector in Glycogen Storage Disease Type II

Abstract: Glycogen storage disease type II (GSD-II; Pompe disease) causes death in infancy from cardiorespiratory failure. The underlying deficiency of acid alpha-glucosidase (GAA; acid maltase) can be corrected by liver-targeted gene therapy in GSD-II, if secretion of GAA is accompanied by receptor-mediated uptake in cardiac and skeletal muscle. An adeno-associated virus (AAV) vector encoding human (h) GAA was pseudotyped as AAV8 (AAV2/8) and injected intravenously into immunodeficient GSD-II mice. High levels of hGAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 51 publications
5
126
1
1
Order By: Relevance
“…Studies demonstrate that expression of the acid alpha glucosidase gene within muscle cells or in some cases secretion of GAA from liver leads to a reduction of the glycogen storage abnormality in the mice. Moreover, these studies showed that the immune response to the expressed enzyme in AAV-treated Pompe mice treated can be reduced in some cases117,121 or be influenced by tissue specific expression 118,119…”
Section: Enzyme Replacement and Other Emerging Therapiesmentioning
confidence: 99%
“…Studies demonstrate that expression of the acid alpha glucosidase gene within muscle cells or in some cases secretion of GAA from liver leads to a reduction of the glycogen storage abnormality in the mice. Moreover, these studies showed that the immune response to the expressed enzyme in AAV-treated Pompe mice treated can be reduced in some cases117,121 or be influenced by tissue specific expression 118,119…”
Section: Enzyme Replacement and Other Emerging Therapiesmentioning
confidence: 99%
“…40 Tissue directed in vivo gene transfer has also been attempted by systemic application of pseudotyped AAV6, AAV8 or AAV9 vectors. 38,39,[42][43][44][45] Besides the fact that there is only a limited number of vector serotypes available, by far lower than the variety of potential tissue targets, these serotype-based targeted vectors also have limited or no specificity for the tissue of interest. In congruence with this assumption, our data showed that the library-derived vectors presented here were more specific than AAV serotype 9 (at least with respect to biodistribution of the genomes), which is known to confer efficient transduction of heart tissue.…”
Section: Transgene Expression In Murine Hearts Following Systemic Admmentioning
confidence: 99%
“…Total RNA extraction and reverse transcription were performed as described [14]. Real-time PCR was performed using LightCycler 480 (Roche Diagnostics, Indianapolis, IN) and primers 5′-TGAGCCCTGA ACCTTCCGATC-3′ (forward) and 5′-GTGCTGTCGTCCATTCTCTGA-3′ (reverse).…”
Section: Quantitation Of Stbd1 Mrnamentioning
confidence: 99%
“…Real-time PCR was performed using LightCycler 480 (Roche Diagnostics, Indianapolis, IN) and primers 5′-TGAGCCCTGA ACCTTCCGATC-3′ (forward) and 5′-GTGCTGTCGTCCATTCTCTGA-3′ (reverse). β-actin was used as internal control [14].…”
Section: Quantitation Of Stbd1 Mrnamentioning
confidence: 99%
See 1 more Smart Citation